(untitled) (Global Journal of Management and Business Research, 2014)
Admitting football as a fundamental element of the economy in capitalist society, we investigate the exploitation of its spectacle in the 1940s. Aiming primarily to stimulate consumption and identification of fans with their clubs, the cartoons of Jornal dos Sports here are analyzed to understand the economic dynamics around the sport. The clubs mascots created by cartoonist Lorenzo Molas would also appear on the advertisements. We will see then how far the concept of Alan Bryman, of "Disneyzation", can be found in the Brazilian case. We will look for traces of this process through thematization and merchandising.